Characterization of an Isopentenyl Diphosphate Isomerase involved in the Juvenile Hormone pathway in Aedes aegypti - Diaz, Miguel (2012)
Isopentenyl diphosphate isomerase (IPPI) is an enzyme involved in the synthesis of juvenile hormone (JH) in the corpora allata (CA) of insects. IPPI catalyzes the conversion of isopentenyl pyrophosphate (IPP) to dimethylallyl pyrophosphate (DMAPP); afterwards IPP and DMAPP condense in a head-to-tail manner to produce geranyl diphosphate (GPP), this head-to-tail condensation can be repeated, by the further reaction of GPP with IPP, yielding the JH precursor farnesyl diphosphate. An IPPI expressed sequence tag (EST) was obtained from an Aedes aegypti corpora-allata + corpora cardiaca library. Its full-length cDNA encodes a 244-aa protein that shows a high degree of similarity with type I IPPIs from other organisms, particularly for those residues that have important roles in catalysis, metal coordination and interaction with the diphosphate moiety of the IPP. Heterologous expression produced a recombinant protein that metabolized IPP into DMAPP; treatment of DMAPP with phosphoric acid produced isoprene, a volatile compound that was measured with an assay based on a solid-phase micro extraction protocol and direct analysis by gas chromatography. A. aegypti IPPI (AaIPPI) required Mg(2+) or Mn(2+) but not Zn(2+) for full activity and it was entirely inhibited by iodoacetamide. Real time PCR experiments showed that AaIPPI is highly expressed in the CA. Changes in AaIPPI mRNA levels in the CA in the pupal and adult female mosquito corresponded well with changes in JH synthesis (Li et al., 2003). This is the first molecular and functional characterization of an isopentenyl diphosphate isomerase involved in the production of juvenile hormone in the CA of an insect.